Molecular Characterization of the First Ebola Virus Isolated in Italy, from a Health Care Worker Repatriated from Sierra Leone - Castilletti, Concetta (Genome Announc, 2015)
Here, we report the complete genome sequence of an Ebola virus (EBOV) isolated from a health worker repatriated from Sierra Leone to Italy in November 2014. The sequence, clustering in clade 3 of the Sierra Leone sequences, was analyzed with respect to mutations possibly affecting diagnostic and therapeutic targets as well as virulence.